2001
DOI: 10.1002/bit.10052
|View full text |Cite
|
Sign up to set email alerts
|

In vitro degradation of a polymeric dye (Poly R‐478) by manganese peroxidase

Abstract: The aim of this study is the evaluation of the enzymatic action of the ligninolytic enzyme manganese peroxidase (MnP), through a suitable addition of H(2)O(2), as a feasible system for the in vitro degradation of complex structures. For this purpose, a highly recalcitrant polymeric dye (Poly R-478) was selected as a model compound. An amperometric technique was used to determine the H(2)O(2) requirement in the decolorization by nonpurified MnP. Two H(2)O(2) supply strategies-fed-batch (every hour) or semiconti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(34 citation statements)
references
References 30 publications
(29 reference statements)
2
31
0
1
Order By: Relevance
“…The intensity of the halo was different among the transformants, SCB2-T3 being the one with the most intense halo. These results are similar to findings by other authors, who screened autochthonous or recombinant fungal strains by the discoloration of Poly R-478 on agar plates and observed halos with different intensities induced by MnP activity [Abdelhafidh et al, 2005;Montiel-González et al, 2009;Moredo et al, 2003;Moreira et al, 2001;Tsukihara et al, 2006].…”
Section: Discussionsupporting
confidence: 81%
“…The intensity of the halo was different among the transformants, SCB2-T3 being the one with the most intense halo. These results are similar to findings by other authors, who screened autochthonous or recombinant fungal strains by the discoloration of Poly R-478 on agar plates and observed halos with different intensities induced by MnP activity [Abdelhafidh et al, 2005;Montiel-González et al, 2009;Moredo et al, 2003;Moreira et al, 2001;Tsukihara et al, 2006].…”
Section: Discussionsupporting
confidence: 81%
“…A disadvantage is the higher costs resulting from the need for extraction and cleaning steps. By contrast, crude culture filtrates offer distinct advantages: they are not as expensive to obtain, and proteins or other factors present in the medium may stabilize crude enzymes, as evidenced by the finding that lower levels of poly R-478 decolorization were obtained with pure MnP of P. chrysosporium than with the nonpurified extracellular liquid [25], and that the highest poly R-478 decolorization rate by crude MnP of P. chrysosporium occurred in parallel with the maximum H 2 O 2 decomposition rate. When H 2 O 2 was depleted, no further decolorization was observed but when H 2 O 2 was supplied semi-continuously, the decolorization rate was much higher [25].…”
Section: Resultsmentioning
confidence: 84%
“…A significant loss of color appeared when DR19 or mixture of dyes was treated with entrapped PGP-Con A complex in the presence of redox mediator, riboflavin in a continuous reactor system (Table 4). It has earlier been reported that the disappearance of peak in visible region was either due to the breakdown of chromophoric groups present in dyes or the removal of pollutants in the form of insoluble products [22].…”
Section: Dye Decolorization By Immobilized Pgp In Batch Process and Amentioning
confidence: 99%